Analysis of antibodies in local and disseminated Neisseria gonorrhoeae infections by means of gel electrophoresis-derived ELISA. - Hadfield, S G (1982)
Major antigens in Neisseria gonorrhoeae were identified by surface labelling the organisms with 125I and electrophoresing extracts in polyacrylamide with sodium dodecyl sulphate. Horizontal slices of the gels were cut out and tested in individual wells against patients' sera using ELISA. Serum from local gonococcal infections reacted with Protein II and, probably, lipopolysaccharide, but not with Protein I in deoxycholate (DOC) extracts and gave no reaction with Triton X-100 extracts. Serum from disseminated gonococcal infections reacted with Protein I in the DOC extract and with pili and a number of undefined possibly cytoplasmic membrane antigens in the Triton X-100 extract. The significance of the results and the potential of the method are discussed.